Direct costs of severe hypoglycemia events in individuals with diabetes mellitus: a perspective from the Colombian health system - a single-center study (2024)
ABSTRACT: Background and aims: Diabetes mellitus is one of the more prevalent chronic diseases globally, and healthcare expenditures for diabetes care are on the rise. Intensive diabetes treatment has been associated with reducing the risk of chronic complications. However, hypoglycemia, the most common adverse effect, poses a significant risk to individuals’ lives and is linked to high costs for healthcare systems. Methods: We conducted a retrospective cross-sectional study to determine direct costs by identifying emergency room visits due to hypoglycemia events using diagnostic codes during January 2017 to June 2019. Direct costs were calculated using billed data from the payer and information on outpatient treatment regimens. Differences in median costs were estimated based on length of stay and type of outpatient treatment. Results: Data from 101 patients and the same number of events were included. Women represented (62.4%) of the patients, the median age was 70 (IQR 59.5–80). Blood glucose levels at admission ranged from 12 mg/dL to 67 mg/dL. Most patients were on insulin for outpatient treatment. The median cost of care per hypoglycemia episode was US $345.35 (IQR US $202–727.8), and the cost per episode was higher in patients treated with regimens that included sulfonylureas. Conclusions: The management of patients admitted to the emergency department with a diagnosis of hypoglycemia places a significant burden on the Colombian healthcare system, primarily due to the associated hospitalization costs. Patients treated with regimens that included sulfonylureas incurred higher costs per episode. Prevention, patient education, and individualized treatment approaches could help alleviate the burden of hypoglycemia on both patients and the healthcare system.